One-pot synthesis of magnesium nanoparticles embedded in a chitosan microparticle matrix: a highly biocompatible tool for in vivo cancer treatment. Issue 2 (15th December 2015) - Martin, Robert. C.; Locatelli, Erica; Li, Yan; Matteini, Paolo; Monaco, Ilaria; Cui, Guozhen; Li, Suping; Banchelli, Martina; Pini, Roberto; Comes Franchini, Mauro
Abstract : A biocompatible nanosystem made up of a chitosan and filled with Mg NPs was synthesized and tested as tool for photothermal therapy. Proof of concept on hcc-bearing mice is presented. Abstract : A novel highly biocompatible nanosystem made up of a chitosan matrix and filled with magnesium nanoparticles was synthesized using a simple and one-pot strategy, and tested as a promising, well-tolerated tool for photothermal therapy. Moreover, in vivo a proof of concept on hepatocarcinoma-bearing mice is presented.